Impact of Positioning Errors on the Dosimetry of Breath-Hold-Based Volumetric Arc Modulated and Tangential Field-in-Field Left-Sided Breast Treatments - Zhao, Yanqun; Diao, Peng; Zhang, Da; Wu, Juxiang; Xin, Xin; Fontanarosa, Davide; Liu, Min; Li, Jie; Orlandini, Lucia Clara (Frontiers in Oncology, 2020)
Heart diseases and cardiovascular events are well known side effects in left-sided breast irradiation. Deep inspiration breath-hold (BH) combined with fast delivery techniques such as volumetric modulated arc therapy (VMAT) or tangential field-in-field (TFiF), can serve as a valid solution to reduce the dose to the heart. This study aims to compare the impact of positioning errors in VMAT and TFiF plans for BH left-sided breast treatments. Ten left-sided breast patients treated in BH with TFiF plan were analyzed in this retrospective study. For each patient a second VMAT reference plan was optimised. For each TFiF and VMAT reference plan, eighteen setup variations were introduced shifting the isocenter in six different directions by 3 mm, 5 mm and 10 mm, and the corresponding 240 perturbed plans were recalculated. The target and organs at risk dose distributions obtained in the different scenarios were compared using dose-volume histograms as dosimetric endpoints; statistical analysis was performed using IBM SPSS v20 software. For 3 and 5 mm isocenter shifts comparable plan quality was obtained with both irradiation techniques (p > 0.05), except for low doses to organs at risk for which higher values (p < 0.05) were obtained for VMAT irradiations. However, if tangential TFiF techniques guarantees an acceptable target coverage for isocenter shifts up to 10 mm, VMAT plans seems to be more sensitive to positioning errors above 5 mm. Objective information on how external stresses impact the dosimetry of the system could be the first step towards personalized radiotherapy.